Impact of Environmental Stresses Onto Transport Properties of Hybrid Perovskite Investigated by Steady State Photocarrier Grating and Steady State Photocurrent Techniques. Issue 11 (19th August 2018) - Longeaud, Christophe; Ramos, F. Javier; Rebai, Amelle; Rousset, Jean
Abstract : In this study, the transport properties of high quality double and triple cation perovskite are explored under different environmental stresses by Steady State Photocurrent (SSPC) and Steady State Photocarrier Grating (SSPG) measurements. SSPG allows a direct measurement of the ambipolar diffusion length that is significantly higher for the cesium containing perovskite (1.4 micron compared to 0.57 micron for a double cation compound). This positive effect is shown to be reversibly annihilated as the samples are put under vacuum, and to be accelerated with the increase of the temperature. The degradation of the material properties appears together with the activation of a defect trap level and a rise of the doping level in the material. This behavior is discussed considering the interaction between the iodine vacancies contained in the perovskite and oxygen which is known to lead to trap passivation. Abstract : The transport properties of double and triple cation perovskite have been explored by SSPG and SSPC, under various conditions. The addition of cesium has been shown to significantly enhance the diffusion length of the perovskite layers, this improvement being reversibly annihilated by a vacuum stress. This behavior can be explained considering the interaction between the iodine vacancies and oxygen.